What happened to Paula: an unsolved death and the danger of American girlhood - Dykstra, Katherine (W. W. Norton & Company, 2021)
"A riveting investigation into a cold case asks how much control women have over their bodies and the direction of their lives. In July 1970, eighteen-year-old Paula Oberbroeckling left her house in Cedar Rapids, Iowa, and never returned. A cold case for fifty years, Paula's story had been largely forgotten when Katherine Dykstra began looking for answers. A woman was dead. Why had no one been held responsible? How could a community give up and move on? Could there ever be justice for Paula? Tracing the knowns and unknowns, Dykstra discovers a girl who was hemmed in by the culture of the late 1960s, when women's rights had been brought to the fore but had little practical bearing on actual lives. The more she learns about Paula, the more parallels Dykstra finds in the lives of the women who knew Paula, the lives of the women in her own family, and even in her own life. Captivating and expertly crafted, What Happened to Paula is a timely, powerful look at gender, autonomy, and the cost of being a woman"--